Prevalensi Mikrofilaria setelah Pengobatan Masal 4 Tahun di Wilayah Kampung Sawah, Kecamatan Ciputat, Tangerang Selatan - Silvia F. Nasution; Evi Ekawati (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2013)
Limphatic filariasis is a target of global diseases elimination promoted by WHO to accomplish by the year of 2020.Until 2008, 316 out of 471 districts/provinces were mapped epidemiologically as endemic areas of filariasis. South Tangerang is one of the district reported as an endemic area of filariasis, with Mf prevalence ranged 1 – 2.4% determined from 2002 to 2009. Some factors play important roles in elimination program of filariasis, such as an appropriate diagnostic and its evaluation, and also annual program of Mass Drug Administration (MDA). In Ciputat area, South Tangerang district, the MDA has been conducted annually since 2009, and evaluation program by finger blood sample was also conducted in 2002 and 2009. Finding result showed prevalence 1.6% of Mf and 8 individu were clinically diagnosed as elephantiasis. Although the MDA has been conducted every year, but the evaluation has not yet been performed after 2009. The Study aimed to evaluate the MDA effect against mikrofilaria rate (Mf) and antigen circulation in perifer blood of people living near by the elephantiasis individu in Kampung Sawah area, Ciputat, South Tangerang. Periferal blood and blood vessel were collected at night from 08.00–10.00 PM. Peripheral blood were directly swab on slide or object glass to overnight preserve for giemsa stain in laboratory. After night preservation, the slide were then identified by microscope to detect microfilaria. The blood vessel were sentrifuged to collect the serum and performed rapid diagnostic test antigen antifilaria IgG4. Finding result of the study determined 95% Mf negative and 72.5 % negative of antigen anti-filaria IgG4. These finding showed that more than 70% of subjects were negative to filarial and its antigen circulation in the blood.This also indicates successfull program of 4 years MDA in this study area to eliminate parasite of filariasis.